Energy cost of individual lower leg muscles in walking : comparison between young and elderly men at different walking speeds - Pincheira, Patricio (2015)
The cost of transport (COT) in elderly subjects is increased in comparison to young adults, independently of the walking speed. The changes in the neuromuscular activity of the lower extremity muscles could explain this phenomenon. The objective of this thesis was to qualitatively compare the muscle activity pattern of the lower extremities between healthy young and elderly subjects, over a range of walking speeds in order to infer the contributions of individual muscles to changes in COT in both age groups.